PENGARUH MODERASI DARI GOOD CORPORATE GOVERNANCE PADA HUBUNGAN ANTARA KONSERVATISME AKUNTANSI DAN MANAJEMEN LABA - Fina Arifiyati; Zaky Machmuddah (Juara: Jurnal Riset Akuntansi, 2019)
The purpose of this research is to examine the moderating effect of good corporate governance on the relationship between accounting conservatism and earnings management. In this research, the types of good corporate governance that will be used are institutional ownership, managerial ownership, proportion of independent board of directors, and audit committees. This research takes manufacturing companies with miscellaneous industry as the sectors listed in Indonesian Stock Exchange, over the period 2012-2016 as the population. Along with that, the samples used are 10 companies with and the total data which has filled the requirements of the purposive sampling’s criteria are 50 data. Meanwhile, the analytical data is tested using two different methods: classical assumption test and hypothetical test with multiple analysis regression. Through this research, it is shown that earnings management significally affected by accounting conservatism. Also, good corporate governance which is represented by institutional ownership moderates the relationship between accounting conservatism on earnings management. On the other hand, managerial ownership, proportion of independent board of directors, and audit committees do not moderate the relationship between accounting conservatism on earnings management. So that the practical implication of this research is that companies must implement accounting conservatism to reduce opportunistic actions of managers who do earnings management, besides that the role of GCG is importance in moderating accounting conservatism towards earnings management.